Meta-analysis of decitabine pretreatment-based allogeneic hematopoietic stem cell transplantation affecting transplantation-related complications and prognosis in patients with malignant hematological disease: Decitabine pretreatment-based allogeneic hematopoietic stem cell transplantation - Li, Lijun; Zhao, Zhirui; Li, Xin (Cellular and Molecular Biology, 2023)
Malignant hematological diseases (MHD) are a kind of bone marrow hematopoietic system disease caused by malignant clonal proliferation, including leukemia, lymphoma, myelodysplastic syndrome, etc. At present, there are too few meta-analyses on the effect of decitabine pretreatment-based allogeneic hematopoietic stem cell transplantation (allo-HSCT) on transplantation-related complications and prognosis of MHD patients. A systematic search of PubMed, MEDLINE, Science Direct, The Cochrane Library, CNKI, and CBM was performed. The relevant literature on decitabine pretreated allo-HSCT for the treatment of MHD was screened, and the screening time was up to May 1, 2023. After extensive investigation, only 5 articles met the criteria. Result: The results of this article showed that the odds ratio of mortality after decitabine conditioning treatment was 2.35, the incidence of complications after transplantation was 1.07, and the survival rate following transplantation was 0.82. Decitabine-based conditioning regimen can reduce the incidence of transplantation-related complications and improve the prognosis of MHD patients receiving allo-HSCT. Although it has limitations, it still has very important clinical implications.